Estudo de viabilidade econômica de microgeração distribuída de energia elétrica a partir de biogás de resíduos bovinos - SOUZA, Frank Leonel Conceição de (2020)
Worldwide, the use of nonrenewable energy sources and its impacts are getting more and more worrisome, culminating in actions seeking the development of new technologies and renewable energy sources. Distinct sources present themselves as renewable and less damning to the environment. Among them, biomass. Biogas – with emphasis to the one generated from farming residues – is interesting due to its potential to, at the same time, avoid new greenhouse gases from being launched on the atmosphere while reducing costs on livestock maintenance, utilizing residues that, before, would be thrown in nature without any treatment. This work, then, talks about the economic viability of generating electric energy with biogas from bovine residues. For that, the production processes and the technologies for converting biogas into electric energy are presented. Then, the costs of implementation and maintenance of the anaerobic digester and of the generator set are calculated. Afterwards, the economy obtained by the implementation is calculated based on a scenario where the energy is provided internally, being, by the property itself through the generator set. For that, scenarios with conventional and white fares are considered, and distinct working periods of the generator set are observed. With this data, the analysis is done – deterministic and probabilistic, this one with the Monte Carlo method – of economic viability of the electricity generating plant.